Intrauterine fetal death due to fetal intracranial hemorrhage associated with maternal vitamin K deficiency: A case report - Koya Yasuda; Soichiro Obata; Eita Kumagai; Takayoshi Iijima; Masafumi Yamamoto; Etsuko Miyagi; Shigeru Aoki (Elsevier, 2023)
Vitamin K deficiency can cause coagulopathy; therefore, supplementation is recommended to prevent intracranial hemorrhage in newborns. Some reports have shown that maternal vitamin K deficiency is associated with intracranial hemorrhage in the fetus. However, no clear guidelines exist for the diagnosis and treatment of maternal vitamin K deficiency to prevent fetal intracranial hemorrhage.We report a case of intrauterine fetal death due to intracranial hemorrhage associated with maternal vitamin K deficiency resulting from hyperemesis gravidarum. In this case, maternal protein induced by vitamin K absence II (PIVKA-II) was high at the time of intrauterine fetal death. Therefore, measuring maternal PIVKA-II levels in high-risk cases may help determine the timing of therapeutic interventions for vitamin K deficiency during pregnancy.